2002
DOI: 10.1023/a:1014022406110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We used a surface forces apparatus to investigate layering transitions and frictional properties of chain alcohol films. All but the last two monolayers, strongly bound to each mica surface can be removed by squeezing. Unlike other systems however, chain alcohol films of undecanol and octanol were found to retain their bulk-like lubrication properties down to a thickness of only one (bi)layer. The transition where this last molecularly thin liquid layer is expelled from the gap proceeds in less than one second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…On the other hand, we would not expect such an increase in T f for water in these materials since R is smaller than 1. 11,12 Recent SFA experiments have confirmed this prediction by showing that water 23,24 and some alcohols (octanol, undecanol 25 ) remain fluid-like, even for confined film thicknesses below 1 nm.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, we would not expect such an increase in T f for water in these materials since R is smaller than 1. 11,12 Recent SFA experiments have confirmed this prediction by showing that water 23,24 and some alcohols (octanol, undecanol 25 ) remain fluid-like, even for confined film thicknesses below 1 nm.…”
Section: Introductionmentioning
confidence: 90%
“…For some polymer–polymer sliding combinations, however, the associated wear is prohibitively high; this is especially true for PTFE. , One approach to addressing the issue of excessive PTFE wear involves the use of confined molecules between the two self-mated polymer surfaces. A number of fundamental studies have been conducted to explain the complex relationships among contact pressure, number of monolayers, and viscosity to the mechanical and frictional responses to shear stress, as well as to characterize the nature of layering dynamics and relaxation times. Here, a more phenomenological approach is taken, and confined fluorocarbon molecules of varying lengths are compressed and sheared between two individually cross-linked PTFE surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This was interpreted as a liquid to solid phase transition occurring at temperatures well above the bulk freezing point. In addition, a number of experiments using activated carbon fibers (ACF) have reported that the freezing temperature in confinement may be lower (water, [29][30][31] octanol 32 and undecanol 32 ) or higher (methanol, 31 carbon tetrachloride, 33 benzene, 34 aniline, 35 OMCTS 36 and cyclohexane 36 ) than the bulk value; in some cases (nitrobenzene 37 ), no appreciable change in the freezing temperature was observed.…”
Section: Introductionmentioning
confidence: 99%